ANALISIS BIBLIOMETRIKA JURNAL KAJIAN INFORMASI DAN PERPUSTAKAAN PERIODE 2016 – 2021 - ROCHANI NANI RAHAYU; SULISNAENI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Bibliometric analysis of the Jurnal Kajian Informasi dan Perpustakaan (JKIP) 2016 – 2021 with the aim of knowing: 1) Number of articles during 2016-2021 on JKPI; 2) The most prolific writer; 3) The pattern of authorship in both journals of collaboration degree; 4).The most productive university; 5) The most productive non-university institution and 6) The city where the author works and 7) The most used keywords. Data was collected through journal.unpad.ac.id/jkip. The data recorded were the number of articles, authors, gender of the author, universities and institutions that contributed, the city where the author worked and keywords. Based on the results and discussion, it is concluded that 89 articles have been published and 148 authors have been published, consisting of 66 men and 82 women. The most productive writer is Pawit M. Yusuf with 8 titles. There are more collaborating writers at JKIP than individual writers, this is reinforced by the collaboration degree value of 0.75. The most productive university is Padjadjaran University. The Indonesian Institute of Sciences is a non-university institution as the largest contributor. The city where most writers work is Bandung. Most keywords are Library